As religiosidades/espiritualidades do (a) paciente e do (a) psicólogo (a): como conciliar? um estudo sobre as percepções de pacientes e profissionais da ABRAPE – Associação Brasileira de Psicólogos Espíritas acerca da abordagem da religiosidade/espiritualidade na psicoterapia - Zilli, Ercilia Pereira (2020)
This work aimed to verify the religious / spiritual (R / E) perceptions and demands of people seeking psychological assistance at ABRAPE – Brazilian Association of Spiritist Psychologists and to evaluate how the psychologists of this institution, who publicly declare their religious affiliation, respond to eventual religious and spiritual demands in the care of these patients taking into account the Psychologist's Code of Ethics. This study also explored how the psychologist's religiosity (when disclosed) can be seen by patients and what role this plays in the patients' perception of the treatment. A quali-quantitative research was carried out using the ABRAPE screening database, which records, among other information, data related to the patient's religious affiliation, R / E demands in the search for care (when present) and perceptions about the approach to the R / E dimension in the psychotherapeutic process, in addition to demographic data (such as age, gender, educational level and household monthly income). All databases available for analysis were used, covering the years 2014, 2015, 2016 and 2017 and the total sample available comprise 4,819 respondents. The second phase of the data collection employed the focus groups methodology with 24 psychologists from ABRAPE. This technique investigates the perceptions, attitudes and social representations displayed by members of specific groups. The findings evidenced the great interest of the patients in approaching their existential needs in light of their R / E, but the response patterns varied according to the religious affiliation. As for the qualitative findings with the psychologists, they reported ease in dealing with R / E issues due to the allowance to discuss this topic in supervisions, as well as the training they receive from the institution. However, they recognize the need for further research in the field of R / E and psychotherapy. The author discusses the implications of the results for clinical practice and the methodological limitations of the study. It is hoped that future studies will contribute to the topics discussed in this doctoral dissertation, either in the researched institution, or in other institutions where psychologists publicly declare their religious affiliation